Replacement of pork fat with sunflower oil in beef frankfurter production - Belichovska Daniela, Pejkovski Zlatko, Belichovska Katerina (Institute of Knowledge Menagament, Skopje, 2018)
In orderto determine the effects of total pork fat replacement with sunflower oil and addition of sodium lactate in the production of frankfurters, four variants of beef frankfurters were produced: 1) with pork fat, 2) with pork fat and lactate, 3) with sunflower oil, and 4) with sunflower oil and lactate. It was found that it is technologically possible complete replacement of pork fat with sunflower oil in the production of frankfurters despite some sensory deficiencies. frankfurters with sunflower oil were more firm, more elastic, with a gummy consistency, brighter in color, with less expressed aroma, but still sensory acceptable. They had better emulsion stability compared to those with pork fat. In the frankfurters with sunflower oil, there was a trend of decreasing the total number and number of lactic acid bacteria (especially after 71 days of storage). In frankfurters containing sodium lactate pH decreasing was slower, they had a lower aw-value and lower TBA-numbers. Purasal S added to the frankfurters in a concentration of 3,79% strengthened the taste of salty and had a mild antioxidant effect
Keywords: frankfurters, pork fat, sunflower oil, characteristics